IDENTIFICATION OF ACTIVE CHEMICAL COMPONENTS OF ETHANOL EXTRACT OF PAINTED NETTLE LEAVES (COLEUS SCUTELLARIOIDES L. BENTH) AGAINST GASTROINTESTINAL INFECTION BACTERIA USING TLCBIOAUTOGRAPHY AND AGAR DIFFUSION METHOD - Junaedi, Fhadillah; Kosman, Rachmat; Herwin, Herwin (Journal Microbiology Science, 2023)
Infectious diseases are one of the public health problems caused by the transmission and multiplication of microorganisms. The research on the antibacterial activity of painted nettle leaves (Coleus scutellarioides L. Benth) extracts was carriedout to examine the activity and chemical components that provide inhibition against gastrointestinal infection bacteria. The extraction of painted nettles leaves performed maceration methd using a solvent of 96%. The extraction results were examined to determine the antibacterial activity at 1% concentration of the test bacteria: Escherichia coli, Salmonella thypi, and Shigella dysenteriae. The results showed that 96% ethanol extract of painted nettle leaves inhibited Escherichia coli, Salmonella thypi, and Shigella dysenteriae. The research conducted using agar diffusion indicated that painted nettleleaf extract showed activity against bacteria and had highly strong potential with diameters of 6-20 mm. The results of Thin Layer Chromatography (TLC) Bioautography test of ethanol extract of painted nettle leaves using chloroform:methanol eluent (3:1) showed inhibition of Escherichia coli, Shigella dysenteriae, and Salmonella thypi at Rf values of 0.90, 0.80, 0.56. Therefore, the identification test confirmed that the chemical componentsproviding antibacterial are from flavonoids, phenols, terpenoids, alkaloids, and steroidsKey words: Identification of chemical components, painted nettle leaves, gastrointestinal bacteria, TLC-Bioautography and Agar diffusion